Biochemical evaluation, molecular characterization and identification of novel yeast strains isolated from Brazilian savannah fruits, chicken litter and a sugar and alcohol mill with biotechnological potential for biofuel and food industries. (October 2018) - Camargo, Janina Zanoni; Nascimento, Valkirea Matos; Stefanello, Isadora; Andrade Silva, Cinthia Aparecida de; Gonçalves, Fabiano Avelino; Perdomo, Igor Chiarelli; Vilela, Danielle Marques; Simionatto, Simone; Pereira, Rodrigo Matheus; da Paz, Marcelo Fossa; Leite, Rodrigo Simões Ribeiro; Lafayette Neves Gelinski, Jane Mary; et al.
Abstract: The aim of this work was to isolate and investigate different yeast strains obtained in the Brazilian Midwest Region. The alcohol fermenting industrial yeast Saccharomyces cerevisiae CAT-1 and another 3 strains previously isolated from a sugar and alcohol mill were also investigated. In this sense, 45 strains were isolated from fruits and chicken litter. They were evaluated through biochemical and molecular analyzes. Then, it was proceded the enzymatic evaluation and the molecular identification of 13 potential strains, selected due to the fermentation capacity of the substrates glucose, fructose and sucrose. One isolate was distinguished by its short time of fermentation ( Candida glabrata Recol 43) and another 3 by their high activity of pyruvate dehydrogenase ( Candida glabrata Recol 41, Candida parapsilosis Recol 29 and Meyerozyma guilliermondii Recol 9). The complete characterization performed here helped to identify novel yeasts with potential for biotechnological applications in biofuel and food industries. Graphical abstract: Highlights: Yeast strains were isolated from Brazilian fruits, chicken litter, and an alcohol mill. 49 yeast strains were characterized through biochemical and molecular analyzes. 13 newly isolates were identified due to the fermentation capacity on different sugars. Potential applications were identified based on characterization.